Practical Medical Management of Crohn's Disease. (7th November 2013) - Baran, Bulent; Karaca, Cetin
Abstract : Crohn's disease is a chronic inflammatory disease of diagnostic and therapeutic challenges. After proper diagnosis, treatment decisions must be made on precise clinical judgment. During the course of the disease there are variable clinical features, so each case must be managed individually. Physicians who care for patients with Crohn's disease should be prepared for treatment options in different states of the disease and possible complications of both the disease and medications. This paper will focus on the management of Crohn's disease. We aim to discuss current treatment options in different presentations of the disease and to provide algorithmic management strategy.